Dysfunction of Mouse Cerebral Arteries during Early Aging. Issue 9 (September 2015) - Balbi, Matilde; Ghosh, Mitrajit; Longden, Thomas A; Vega, Max Jativa; Gesierich, Benno; Hellal, Farida; Lourbopoulos, Athanasios; Nelson, Mark T; Plesnila, Nikolaus
Aging leads to a gradual decline in the fidelity of cerebral blood flow (CBF) responses to neuronal activation, resulting in an increased risk for stroke and dementia. However, it is currently unknown when age-related cerebrovascular dysfunction starts or which vascular components and functions are first affected. The aim of this study was to examine the function of microcirculation throughout aging in mice. Microcirculation was challenged by inhalation of 5% and 10% CO2 or by forepaw stimulation in 6-week, 8-month, and 12-month-old FVB/N mice. The resulting dilation of pial vessels and increase in CBF was measured by intravital fluorescence microscopy and laser Doppler fluxmetry, respectively. Neurovascular coupling and astrocytic endfoot Ca 2+ were measured in acute brain slices from 18-month-old mice. We did not reveal any changes in CBF after CO2 reactivity up to an age of 12 months. However, direct visualization of pial vessels by in vivo microscopy showed a significant, age-dependent loss of CO2 reactivity starting at 8 months of age. At the same age neurovascular coupling was also significantly affected. These results suggest that aging does not affect cerebral vessel function simultaneously, but starts in pial microvessels months before global changes in CBF are detectable.